2020
DOI: 10.1111/add.15006
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a Group psychological intervention to increase locus of control for alcohol consumption among Alcohol‐Misusing Short‐term (male) Prisoners (GASP)

Abstract: Background and aim Reducing alcohol misuse by male prisoners is an important global issue. Control of drinking behaviour could be a useful target for intervention in this population, and locus of control could be a causal factor in this. We aimed to assess the effect of a clinical psychologist‐facilitated group intervention on male prisoners’ locus of control of drinking behaviour. Design A two‐arm, single‐site, open, randomized controlled trial. Setting A category B local training prison in South Wales, housi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The sample size of the participants in the included studies ranged from 34 to 759. Twenty studies were conducted in high-income countries (USA 10, 18 , 19 , 21 28 UK 3, 29 31 Netherlands 1, 32 Norway 1, 33 Spain 2, 34 , 35 China 2, 36 , 37 and Sweden 1 38 ; one study was conducted in an upper-middle-income country Malaysia). 39 There were no studies that were conducted in middle-income or lower- income countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size of the participants in the included studies ranged from 34 to 759. Twenty studies were conducted in high-income countries (USA 10, 18 , 19 , 21 28 UK 3, 29 31 Netherlands 1, 32 Norway 1, 33 Spain 2, 34 , 35 China 2, 36 , 37 and Sweden 1 38 ; one study was conducted in an upper-middle-income country Malaysia). 39 There were no studies that were conducted in middle-income or lower- income countries.…”
Section: Resultsmentioning
confidence: 99%
“…The intervention group underwent different therapies such as motivation enhancement therapy (MET), 17 , 18 , 21 , 28 , 40 seeking safety program, 41 cognitive behavior therapy (CBT), 42 interpersonal therapy (IPT), 25 acceptance and commitment therapy (ACT), 34 , 35 cognitive behavioral suicidal prevention therapy (CBSP), 43 group interpersonal psychotherapy, 24 , 44 music therapy, 33 , 37 art therapy, 36 group psychological intervention, 31 and mindfulness-based relapse prevention intervention. 27 The average duration of intervention in the studies ranged from 10 min to 120 min, with the frequency of sessions being one per week to six per week across one month to six months.…”
Section: Resultsmentioning
confidence: 99%
“…36 Although CSEs have received less attention in the occupational health literature, meta-analytic reviews also have established the components of CSE as predictors of burnout, 26 and other research has shown that each of the components of CSE may be influenced by interventions. [37][38][39][40] The Present Study Because CSE, optimism, and mindfulness are conceptually related indicators of dispositional resilience, we sought to assess the relative contribution of each of these characteristics to predicting occupational health outcomes. We investigated five outcomes that reflect three important components of EM physicians' work experiences: fatigue, turnover intentions, and productivity.…”
Section: Personal Resources and The Capacity For Resiliencementioning
confidence: 99%
“…Not surprisingly then, high CSE individuals also tend to perform better and have more positive perceptions of their work environment 36 . Although CSEs have received less attention in the occupational health literature, meta-analytic reviews also have established the components of CSE as predictors of burnout, 26 and other research has shown that each of the components of CSE may be influenced by interventions 37–40 …”
Section: Personal Resources and The Capacity For Resiliencementioning
confidence: 99%